Relationship of mother's psychological condition to smooth milk production in breastfeeding mothers - Ayu Devita Citra Dewi; Susmita (Science Midwifery, 2023)
Milk production is strongly influenced by psychological factors. Mothers who experience emotional disturbances can interfere with the let down reflex process which results in the milk not coming out, so the baby does not get enough milk and the baby will continue to cry. The research design used an analytic survey with a cross-sectional approach. The study was conducted at the 23 Ilir Health Center in Palembang with samples taken from all populations according to the criteria. The results of the study found 13 respondents (81.2%) of the 37 respondents with unfavorable psychological conditions so that breast milk was not smooth, 15 (71.4%) of 37 respondents with good psychological conditions so that breast milk production was smooth. The statistical test results obtained a p value = 0.004 less than α = 0.05 which means Ho = rejected, so it is stated that there is a significant relationship between breast care and smooth milk production. Odds Ratio (OR) of 10.33 (95% CI = 2.24-52.19) which means that mothers with unfavorable psychological conditions with an odds ratio of 10.33 can affect the smooth production of breast milk. Based on the research results, there is a relationship between the psychological condition of the mother and the smooth production of breast milk, so it is very important to maintain the psychological condition of the mother to remain happy and happy during the breastfeeding process.